The Concept Of Family, Community And Education Relations In Islam - Dhia Alfa Della; Ririn Khairunnisa; Taufik Abdullah Attamimi; Uswatun Hasanah (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This article aims to examine the concept of the relationship between family, society, and education from an Islamic perspective. The background of the study stems from increasing socio-cultural challenges due to globalization, which weaken spiritual and moral values in children's education. In Islam, education is not solely the responsibility of formal institutions such as schools but is primarily the duty of the family as the first educational institution, reinforced by the surrounding community. This research uses a qualitative approach with library research methods, analyzing classical and contemporary Islamic educational literature. The data were analyzed using a descriptive-analytical method to develop a conceptual synthesis. The findings show that synergy among family, society, and school is crucial in shaping a child's character in a holistic way—spiritually, intellectually, and socially. Each element plays a complementary role in forming integrated education: the family lays the foundation, schools develop intellectual potential systematically, and society provides a space for value actualization. This study highlights the importance of active collaboration among these three institutions in nurturing a morally sound generation in the face of modern-day challenges.